Reverse Extensions and Multi-Layered Experiences of Harmony in Drake’s Harmonic Loops - Hudson, Stephen (Current Musicology, 2023)
Drake's music features both lyrics and harmonies that often appear multilayered, ambiguous, and conflicted to listeners. Sometimes these multilayered harmonies are created through what I call "reverse extensions," where the bass line moves one or more thirds below the root of the chord in a fixed harmonic loop. These reverse extensions can sometimes be heard as a "harmonic-bass divorce" (de Clercq 2019) in which the bass line moves independently from the harmonic layer. However, I argue that they often can also be heard as single integrated harmonies, and that these plural hearings draw on intra- and inter-textual memory to create multilayered harmonic experiences which help evoke the conflicted and ambivalent feelings that Drake's lyrics are famous for. The plural identities of these chords can be understood by adapting elementary concepts from jazz theory, in which extended chords can be mimicked by or substituted with "slash chords" that add a bass note below the base triad; for example, G/A (G major triad with A in the bass, or AGBD) sounds like Am11 (ACEGBD). This chord sometimes seems to convey a double function of both G and Am. Relationships like this create an "extension-related family" of chords which often easily substitute for one another in chord progressions. I argue that by enumerating possibilities for chord substitutions, and plural hearings of extended chords, reverse extensions are an “enactive music theory” which frames chord identity as a structure subjectively enacted by an individual, rather than an objective property inherent “the music itself.”